Keys to Unlock the Enigma of Ocular Toxocariasis: A Systematic Review and Meta-analysis. (17th November 2021) - Badri, Milad; Eslahi, Aida Vafae; Olfatifar, Meysam; Dalvand, Sahar; Houshmand, Elham; Abdoli, Amir; Majidiani, Hamidreza; Eslami, Ali; Zibaei, Mohammad; Johkool, Morteza Ghanbari; Taghipour, Ali; Hashemipour, Sima
ABSTRACT: Purpose: Ocular toxocariasis (OT) is a zoonotic infection caused by larval stages of Toxocara canis and T. cati . The current review and meta-analysis aimed to evaluate the global prevalence of OT. Methods: Five English (PubMed, Scopus, Science Direct, Web of Science, and Google Scholar) databases were explored and 101 articles met the inclusion criteria. Results: The pooled prevalence (95% confidence interval) of OT was higher in immunological studies (9%. 6–12%) than in studies that applied ophthalmic examination (1%. 1–2%). The lower middle-income level countries had the highest prevalence (6%. 2–12%) as well as the African region (10%. 7–13%). The highest infection rate (4%. 2–7%) was detected in the 1–25 mean age group. Conclusion: Regular anthelminthic treatment of cats and dogs, and removal of animal feces from public places must be considered.